Analysis of Student Mathematical Resilience in Pure Mathematics-Based Courses - Arta Ekayanti; Uki Suhendar; Erika Eka Santi (MultiTech Publisher, 2023)
Mathematical resilience is a person's ability to handle difficulties in solving problems related to mathematical concepts. The purpose of this study is to analyze students' mathematical resilience in pure mathematics-based courses. This research is a quantitative qualitative research, with students of the Mathematics Education Study Program at Muhammadiyah University of Ponorogo who have and/or are taking pure mathematics-based courses in the odd semester of the 2022/2023 Academic Year as the research subject. Mathematical resilience’s data was taken by using a questionnaire instrument. The results of the study show that classically the majority of students have moderate category of mathematical resilience. If viewed from each indicator, the results of the study show that in indicators 1, 2, 5 and 6 the majority of students have medium category resilience. While indicators 3, 4, 7 and 8, the majority of students are in the high category. In indicator 9, the number of students with high category mathematical resilience is the same as the number of students with moderate category of mathematical resilience